Community empowerment in Ngabab village through the DeWe@n program: analysis of the ACTORS framework - Shofa, Abdullah; Effendy, Syazani Mumtaz Azmy; Pusposari, Luthfiya Fathi (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study aims to analyze the community economic empowerment strategy through the DeWe@n Educational Tourism Village program in Ngabab Village, Pujon District, Malang Regency, with a focus on the application of the ACTORS framework (Authority, Confidence, Trust, Opportunities, Responsibilities, and Support). This study uses a qualitative approach with a case study design, involving 16 key informants consisting of village officials, MSMEs, and local communities. Data were collected through participant observation, semi-structured interviews, and documentation studies, then analyzed using the Miles and Huberman interactive model. The results show that the ACTORS framework plays a significant role in strengthening community empowerment strategies. The authority dimension is realized through granting authority to the community to manage tourism activities independently. This confidence is evident in the increasing confidence of MSMEs and youth in innovating and interacting with tourists. Trust grows through a relationship of mutual trust between the village government and residents that forms social solidarity. Opportunities are seen in the emergence of various new economic opportunities based on local products, while responsibilities reflect a sense of ownership towards the community who travel, although a formal tourism management institutional structure has not been permanently established. Meanwhile, support comes through collaboration between village governments, educational institutions, and private partners. Contextually, this research confirms that the ACTORS implementation model is effective in encouraging participation, building social trust, and strengthening village economic independence based on local potential in a sustainable manner.